Perilaku Gaya Hidup Konsumtif Pada Remaja Pengguna Media Sosial Instagram Di Desa Uloe Kabupaten Bone - Andi Almadani Marennu Okarniatif; Firdaus W. Suhaeb (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This study aims to find out: 1) How is the consumption behavior that occurs in adolescents who use the Instagram social network in Uloe Village, Bone Regency. 2) What are the patterns of adolescent consumptive behavior in using the Instagram social network in Uloe Village, Bone Regency. This research uses a descriptive research method with a qualitative research type. The number of informants in this study were 7 people who were determined by sampling techniques with criteria 1) young Instagram users with a collection of more than 10 pieces of clothing, 2) young Instagram users have more than one cell phone. Records collection techniques used in this research are observation, interview and documentation methods. The three-step qualitative data analysis technique includes gathering information, presenting information, and drawing conclusions. The results of this study indicate that: 1) consumer behavior that occurs among adolescents who use the Instagram social network in Uloe Village, Bone Regency is (a) interested in packaging, (b) shopping for appearances, (c) social popularity, (d) compliance, curiosity about the products offered with Instagram ads. 2) The pattern of consumptive behavior of adolescents using the Instagram social network in Uloe Village, Bone Regency, namely (a) unplanned purchases (b) excessive purchases (c) seeking pleasure.